First defection of the equine herpesvirus 1 neuropathogenic variant in Brazil - Mori, E.; Borges, Alexandre Secorun [UNESP]; Delfiol, D. J Z [UNESP]; Oliveira Filho, José Paes de [UNESP]; Goncalves, Roberto Calderon [UNESP]; Cagnini, D. Q. [UNESP]; Lara, M. C C S H; Cunha, E. M S; Villalobos, E. M C; Nassar, A. F C; Castro, A. M M G; Brandao, P. E.; et al. (My University, 2011)
This report describes the first detection of an equine herpesvirus 1 (EHV-1) neuropathogenic variant (G 2254/D 752) in Brazil from a case of fatal equine herpesvirus myeloencephalopathy (EHM) in a mare. The results of nucleotide sequencing of the EHV-1 ORF30 gene showed that two other Brazilian EHV-1 isolates from EHM cases are representatives of the non-neuropathogenic variant (A 2254/N 752), suggesting that other unidentified factors are probably also involved in the neuropathogenicity of EHV-1 in horses. These findings will contribute to the epidemiological knowledge of EHV-1 infection in Brazil.
Keywords: Brazil; DNA polymerase gene; Equine herpesvirus 1; Neurological disease; Neuropathogenic; Equid herpesvirus 1; Equidae; Equine herpesvirus sp.; Herpesviridae; Human herpesvirus 1; animal; animal disease; animal euthanasia; brain; case report; Equine herpes virus; fatality; female; genetics; herpes virus infection; horse; horse disease; isolation and purification; myelitis; pathogenicity; pathology; spinal cord; virology; virus encephalitis; Animals; Brain; Encephalitis, Viral; Euthanasia, Animal; Fatal Outcome; Female; Herpesviridae Infections; Herpesvirus 1, Equid; Horse Diseases; Horses; Myelitis; Spinal Cord